Description of late onset neutropenia in indolent lymphoma patients treated with bendamustine plus rituximab. Issue 1 (7th July 2017) - Verriere, B.; Gastaud, L.; Chamorey, E.; Peyrade, F.; Deletie, E.; Bouredji, K.; Quinsat, D.; Schiappa, R.; Thyss, A.; Re, D.
Abstract: Bendamustine (B) associated with rituximab (R) is widely described in literature for the management of patients with chronic lymphoid leukaemia (CLL) and indolent non‐Hodgkin lymphoma. Safety data regarding late hematotoxicity such as late onset neutropenia (LON) are scarce. The aim of our study was to assess the incidence and to identify risk factors for LON in patients with indolent non‐Hodgkin lymphoma and CLL treated with B and R (B‐R). One hundred forty five patients were treated with B‐R as first or second line. Patients with neutropenia prior induction treatment, treated beyond second line and relapsing within 3 months after the end of induction treatment, were excluded. Patients receiving at least 1 cycle of B‐R and having LON during follow‐up period were included and considered as eligible for toxicity assessment. A complete blood count was performed 4 weeks after the last cycle of induction treatment and thereafter every 3 months for 1 year. Thirty six patients were identified in our cohort (incidence of 25%), mostly affected by CLL (n = 11) and follicular lymphoma (FL) (n = 15). During follow‐up, 84 events of LON were recorded, 61% and 39% were of grades 1/2 and 3/4, respectively. No episode of febrile neutropenia was documented. Amongst 13 of the 15 patients with FL undergoing R maintenance, 8 had treatment discontinuation because of LON. Median time for LON (grade > 2) and time to recovery (grade < 3) were of 11.2 and 17.3 weeks, respectively. One year after B‐R induction, LON persisted in 4 patients. The risk of LON was increased both in patients with FL or CLL and performance status >1. The LON in B‐R treated patients is clinically relevant. Close clinical and biological follow‐up and treatment prophylaxis (eg, valaciclovir and cotrimoxazole) especially for FL patients undergoing maintenance with R monotherapy seems relevant.